Site Design dan Interactive melalui Instagram: Studi Kasus Pada Usaha Mikro Kecil Menengah Kopi Cimanggu - Dedy Ardiansyah Ramadhan; Maria Fitriah; Sukarelawati Sukarelawati (LPPM STIKI Malang, 2024)
This research aims to explore the role of Instagram in the digital marketing strategy adopted by Small and Medium Enterprises (SMEs) such as Kopi Cimanggu, focusing specifically on Site Design and Interactive aspects. The study reveals the significant relevance of social media, particularly Instagram, in enhancing visibility and strengthening brand identity for small businesses in the digital era. Employing a qualitative descriptive methodology, in-depth interviews were conducted with the owners of Kopi Cimanggu and digital marketing practitioners to detail their Instagram usage strategies. Key findings highlight that compelling visual design and effective interaction on the Instagram platform play a crucial role in attracting and retaining consumer interest. The success of Instagram utilization by Kopi Cimanggu is evidenced in enhancing product visibility and strengthening customer relationships. Thus, this research not only observes the positive impact of social media on SME marketing but also provides practical guidance for other SMEs in developing their digital marketing strategies. In conclusion, this study contributes valuable insights into the profound understanding of social media utilization, particularly Instagram, in digital marketing for SMEs. The research implications indicate that SMEs can leverage social media platforms, such as Instagram, as effective tools to expand market reach and significantly enhance customer engagement.